(untitled) (Canadian Medical Education Journal, 2018)
Background: Residency programs are facing significant restructuring through the “Competence by Design” (CBD) framework proposed by the Royal College of Physicians and Surgeons of Canada (RCPSC). Our goal was to establish the competencies to be acquired during the transition to a senior role within Internal Medicine (IM) training. Methods: Using a modified Delphi technique, practicing IM physicians and recent graduates were polled to develop consensus on the required competencies to effectively transition from junior to senior medical resident. Participants rated each competency on a three-point Likert scale. Each competency was linked to an Entrustable Professional Activity (EPA) identified by the RCPSC IM Specialty Committee. Results: A total of eighteen participants took part in item generation (16% response rate) and nineteen in the initial ranking with seventeen completing all three iterations (89% completion rate). Eighty-three competencies were identified during questionnaire development. A final list of seventy-seven competencies reached consensus after three rounds. Most competencies matched to core of discipline EPAs. Conclusion: This consensus-based list of competencies will help create a framework and tools for the assessment of junior residents as they prepare to transition to the role of senior in the new CBD curricula for IM trainees at our institution.